Anti-Alzheimer and Antioxidant Activity of Celastrus paniculatus Seed: Antioxidant activity of Celastrus paniculatus - Badrul Alama; Ekramul Haque (Iranian Journal of Pharmaceutical Sciences, 2011)
The crude methanolic extract of the seeds of Celastrus paniculatus along with its organic soluble fractions were tested for their possible antioxidant and antialzheirmer (AD) activity. The extracts showed prominent DPPH free radical scavenging activity, inhibiting activity of authentic peroxynitrite (ONOO-) and inhibition of total reactive oxygen species (ROS) generation. In DPPH radical scavenging assay, the EtOAc fraction showed the highest activity with a IC50 value of 25.92±1.02 μg/ml whereas aqueous fractions had no activity at all within the tested concentration. Scavenging of the authentic ONOO- system, all extract/fractions showed good activity and among them, EtOAc fraction had the highest activity with a IC50 value of 15.79±0.18 μg/ml. EtOAc fraction also showed significant (p<0.001) inhibitory activity against the total ROS generation which was almost similar with that of the positive control Trolox (IC50 16.79±0.19 μg/ml). All extract/fractions exhibited statistically significant (p<0.001) cholinesterases (ChEs) inhibitory effects with IC50 values ranging between 134.7-227.5 μg/ml for AChE and 209.6-562.1 μg/ml for BChE.